The political economy of colonialism in Ghana : a collection of documents and statistics, 1900-1960 - Kay, Geoffrey B.; Hymer, Stephen (Cambridge Eng. : At the University Press, 1972)
This volume is a collection of source material relating to the Ghanaian economy and economic policy in the heyday of colonial rule statistics between 1900 and 1960. Part 2 contains 40 official documents, drawn mainly from the period 1920-50. The first chapter on general economic policy is followed by others on finance, transport, agriculture - including cocoa - and education. Part 3 consists of a statistical abstract for the years I900-60, under the headings of population, wages, development plans, external trade, public finance, transport and communications, education, and miscellaneous.
Includes bibliographical references and index.
lje 02/10/2018
Loans
Keywords: Economic development; Ghana